2010
DOI: 10.1016/j.ydbio.2009.12.004
|View full text |Cite
|
Sign up to set email alerts
|

UNC-83 coordinates kinesin-1 and dynein activities at the nuclear envelope during nuclear migration

Abstract: Nuclei migrate during many events, including fertilization, establishment of polarity, differentiation, and cell division. The C. elegans KASH protein UNC-83 localizes to the outer nuclear membrane where it recruits kinesin-1 to provide the major motor activity required for nuclear migration in embryonic hyp7 cells. Here we show that UNC-83 also recruits two dynein-regulating complexes to the cytoplasmic face of the nucleus that play a regulatory role. One consists of the NudE homolog NUD-2 and the NudF/Lis1/P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
141
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(144 citation statements)
references
References 66 publications
(96 reference statements)
3
141
0
Order By: Relevance
“…The concept of nuclear positioning by gliding along microtubules is supported by previous studies demonstrating an interaction of kinesin and dynein-dynactin motor complexes with mammalian nesprins 1, 2 and 4, and with the related KASH-domain proteins ZYG-12 and UNC-83 in C. elegans (Malone et al, 2003;Roux et al, 2009;Zhang et al, 2009;Fridolfsson et al, 2010;Yu et al, 2011;Holzbaur, 2012, 2015). In myotubes, we propose that this interaction is indirect, mediated by nuclear-envelope-bound centrosome proteins, because the depletion of the centrosome protein PCM-1 induces loss of dynactin and kinesin subunits from the nuclear surface.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The concept of nuclear positioning by gliding along microtubules is supported by previous studies demonstrating an interaction of kinesin and dynein-dynactin motor complexes with mammalian nesprins 1, 2 and 4, and with the related KASH-domain proteins ZYG-12 and UNC-83 in C. elegans (Malone et al, 2003;Roux et al, 2009;Zhang et al, 2009;Fridolfsson et al, 2010;Yu et al, 2011;Holzbaur, 2012, 2015). In myotubes, we propose that this interaction is indirect, mediated by nuclear-envelope-bound centrosome proteins, because the depletion of the centrosome protein PCM-1 induces loss of dynactin and kinesin subunits from the nuclear surface.…”
Section: Discussionmentioning
confidence: 85%
“…In various studies on non-muscular cells, nesprins have been implied to interact with the actin cytoskeleton (Starr and Han, 2002;Zhen et al, 2002;Padmakumar et al, 2004). In addition, nesprins and related proteins have been shown to interact with components of the microtubule network, such as kinesin, dynein and dynactin, and with the centrosome (Malone et al, 2003;Roux et al, 2009;Zhang et al, 2009;Zhou et al, 2009;Fridolfsson et al, 2010;Yu et al, 2011;Holzbaur, 2012, 2015). Several groups have reported that proteins of the centrosome, such as PCM-1, pericentrin and Îł-tubulin, are relocated from the pericentriolar material to the nuclear envelope upon onset of myoblast differentiation, and that a substantial amount of microtubules grow from the nuclear surface following this reorganization (Tassin et al, 1985a;Bugnard et al, 2005;Srsen et al, 2009;Fant et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Rab6B-BicD1 interaction regulates retrograde membrane transport in human neurites (Wanschers et al, 2007). Fly and worm Bic-D genes are also involved in nuclear migration in photoreceptors, oocytes and hypodermal precursor cells (Swan et al, 1999;Swan and Suter, 1996;Fridolfsson et al, 2010), and Bic-D also dynamically regulates transport of lipid droplets (Larsen et al, 2008). Given the involvement of Bic-D in the localization of surprisingly diverse cargoes, we searched for adaptor proteins that mediate cargo binding as well as for novel cargo molecules.…”
Section: Introductionmentioning
confidence: 99%
“…LC8 is conserved throughout eukaryotic genomes (5). As a part of the dynein motor, LC8 is important for fundamental cellular processes, such as tubulin minus-enddirected intracellular transport, chromatid separation during mitosis, and nuclear migration (6), as well as flagellum-specific functions, namely, motility, intraflagellar transport (7), and ciliogenesis (8,9). While not essential in Saccharomyces cerevisiae (10), mutation or knockdown of LC8 is embryonic lethal in animals (8,9,11,12).…”
mentioning
confidence: 99%